Remote Health Monitoring of Wind Turbines Employing Vibroacoustic Transducers and Autoencoders - Czyżewski, Andrzej (Frontiers in Energy Research, 2022)
An implementation of remote monitoring technology for real wind turbine structures designed to detect potential sources of failure is described. An innovative multi-axis acoustic sensor measuring acoustic intensity as well as previously known accelerometers were used for this purpose. The scientific experiment had to overcome many organizational challenges but resulted in data gathering enabling the use of an artificial neural network, of autoencoder-type, which proved to be highly effective when applied to the automatic prediction of failures that may cause potential mechanism failures. The article starts with a literature review on vibroacoustic diagnostics, shows the engineered portable measuring station, presents the developed solutions in the field of intelligent signal processing, and then discusses the outcomes of the research stage, together with achieved results and conclusions drawn from the implemented project.